Antioxidant assessment of characterised essential oils from Calophyllum inophyllum Linn using 2,2-diphenyl-1-picrylhydrazyl and hydrogen peroxide methods - Emmanuel O. Ojah; Dorcas O. Moronkola; Paul M. Osamudiamen (AOSIS, 2020)
Background: Oxidative stress is a multifactorial global health disorder that disrupts all levels of cell function. Therefore, therapeutic intervention using reliable, affordable and non-toxic natural sources is crucial. Aim: The aim of this article was to determine the chemical constituents and antioxidant activity of 10 essential oils (EOs) from Calophyllum inophyllum Linn using 2,2-diphenyl-1- picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2) methods. Setting: Plant sample was collected at the Botanical Garden, University of Ibadan, Nigeria. Extractions and antioxidant assay were performed at the Organic Chemistry Research Laboratory, University of Ibadan, Nigeria. Gas chromatography-mass spectrophotometry (GC-MS) analysis was carried out at the School of Pharmacy, University of Camerino, Italy. Methods: The chemical constituents were determined using GC-MS. The oils were extracted using an all-glass Clevenger-type apparatus and the antioxidant activity was determined using DPPH and hydrogen peroxide assays. Results: A total of 102 compounds were identified in EOs from C. inophyllum Linn, which are mostly monoterpenes, sesquiterpenes and their oxygenated derivatives. The oils exhibited concentration-dependent activity with reference to standard synthetic antioxidants. Root wood had the highest antioxidant activity with the half maximal inhibitory concentration (IC50) of 3.19 mg/mL compared to ascorbic acid (2.84 mg/mL) and butylated hydroxyl anisole (BHA) (2.97 mg/mL). In the H2O2 antioxidant assay, root wood had the highest antioxidant activity with IC50 of 2.78 mg/mL compared to ascorbic acid (2.20 mg/mL) and BHA (2.92 mg/mL). Conclusion: The in vitro chemical compositional analysis of EOs from C. inophyllum Linn confirms the presence of compounds responsible for the antioxidant properties of the plant.